Menumbuhkan Budaya Literasi Bahasa Indonesia Melalui Metode Bernyanyi Gerak Dan Lagu Anak Usia 4-6 Tahun Di Sanggar Bimbingan Kepong Kuala Lumpur Malaysia - Safitri, Linda; Pujiati, Desti (Universitas Nusantara PGRI Kediri, 2023)
This research discusses literacy culture with the aim of this study is to find out the state of literacy education in the Sanggar Bimbingan Kepong, Malaysia, as well as habituation in Growing Indonesian Language Literacy Culture. The method used in this research is descriptive qualitative. The subjects of this study were 10 children aged 4-6 years, in Kepong Village, Kuala Lumpur, Malaysia. Data collection techniques used in this study were observation, interviews, and questionnaire data. The assessment instrument used is the observation sheet to foster an Indonesian language literacy culture. The condition of immigrant citizens who do not have official documents has made immigrant children not able to register for formal schools in Malaysia. To overcome this, the leadership of Muhammadiyah Malaysia opened the Sekolah Sanggar Bimbingan Kepong with the aim that immigrant children who do not have documents can study in the Sekolah Sanggar Bimbingan Kepong. Because of that, the researcher was sparked to examine the state of literacy in the Sanggar Bimbingan Kepong, Kuala Lumpur, Malaysia.